Factors affecting general practitioners’ referrals of patients to hip and knee arthroplasty: a focus group study from Northern Norway - Bodil H. Blix; Veronica Hovind; Tor Ingebrigtsen (BMC Health Services Research)
Abstract Background In Norway, patients have the right to choose their healthcare provider for elective specialized treatments, including the approximately 20,000 annual hip and knee arthroplasty surgeries. There is considerable regional variation in mobility – ‘patient leakage’ – out of a regional health authority for patients seeking these surgical procedures. General practitioners play a vital role in this decision-making process, acting as gatekeepers in referring patients to specialized healthcare. This study investigates the factors influencing Norwegian general practitioners’ referral decision for hip and knee arthroplasty surgeries. Methods We conducted five focus group interviews with 28 general practitioners across various municipalities in Northern Norway, selected based on differing levels of ‘patient leakage’ according to the Norwegian Patient Registry. The thematic analysis focused on: 1. The involvement of general practitioners, patients, and other parties in the decision-making process, and 2. The impact of interpersonal, service-related, and broader societal factors on these decisions. Results The analysis identified four main themes: 1. Navigating referral decisions, 2. Patients’ expectations, knowledge, and beliefs, 3. Service factors affecting referral practices, which includes sub-themes such as hospital reputation, general practitioners’ familiarity with specialists, selection bias, and concerns for post-operative care, and 4. Societal and structural factors, including geographic logistics and local hospital disputes. Conclusion The decision-making process for selecting treatment providers is complex and influenced by multiple intersecting factors. While general practitioners are crucial in guiding patient referrals, many elements contributing to ‘patient leakage’ are beyond their control. Our results suggest that policies to address patient leakage should encompass a broader, cross-sectoral approach rather than focusing solely on healthcare services.